2018
DOI: 10.3390/nu10030293
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Effective Interventions Promoting Healthy Eating for Pre-Schoolers in Childcare Settings: An Umbrella Review

Abstract: Early Childhood Education and Care (ECEC) settings have a pivotal role in shaping children’s dietary food habits by providing the contextual environment within which they develop these behaviours. This study examines systematic reviews for (1) the effectiveness of interventions to promote healthy eating in children aged 2–5 years attending centre-based childcare; (2) intervention characteristics which are associated with promoting healthy eating and; (3) recommendations for child-health policies and practices.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
139
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(151 citation statements)
references
References 93 publications
(233 reference statements)
3
139
0
1
Order By: Relevance
“…This is an example how works the model of pediatric obesity proposed by Smith et al (2018), and how the cumulative exposure to risks and dysregulation in response to stress contribute to pediatric obesity (Evans & Pilyoung, 2013). This sample presents opposition coping strategies, with emotional reactions of sadness and fear, perceiving the stressors as a threat to their need for autonomy; children are less involved in family meals; present greater difficulty in food control, use food as a reward, being in chronic stress conditions, less likely to be adherent to treatment, and requiring multi-professional interventions with health professionals in the social and mental health spheres (Campos et al, 2017;Fenner et al, 2013;Filgueiras & Sawaya, 2018;Matwiejczyk et al, 2018). Expanding the repertoire of coping, as presented by families at medium psychosocial risk ("Targeted") may be a way to increase adherence to treatment; as well as encouraging physical activity as a way of promoting health and preventing the child´s overweight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an example how works the model of pediatric obesity proposed by Smith et al (2018), and how the cumulative exposure to risks and dysregulation in response to stress contribute to pediatric obesity (Evans & Pilyoung, 2013). This sample presents opposition coping strategies, with emotional reactions of sadness and fear, perceiving the stressors as a threat to their need for autonomy; children are less involved in family meals; present greater difficulty in food control, use food as a reward, being in chronic stress conditions, less likely to be adherent to treatment, and requiring multi-professional interventions with health professionals in the social and mental health spheres (Campos et al, 2017;Fenner et al, 2013;Filgueiras & Sawaya, 2018;Matwiejczyk et al, 2018). Expanding the repertoire of coping, as presented by families at medium psychosocial risk ("Targeted") may be a way to increase adherence to treatment; as well as encouraging physical activity as a way of promoting health and preventing the child´s overweight.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the parental stressors and coping with overweight/obesity treatment, we used the Interview on Parental Coping with Overweight/Obesity Child adapted from Guimarães (2015) and based on the Motivational Theory of Coping Scale-12 (Lees, 2007). This protocol contains three domains: 1) Caregiver and child identification data, date/time of administration; e) Demand (identification of stressors) and 3) Coping process.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous qualitative studies have shown that childcare providers understand that nutrition and physical activity are important for the health of the child, but barriers to implementation include parent cooperation and staff training (Dev et al, ; Lindsay, Salkeld, Greaney, & Sands, ; Lyn, Evers, Davis, Maalouf, & Griffin, ; Rosenthal, Crowley, & Curry, ; Sisson, Smith, & Cheney, ). As the field is currently evolving from the gathering of an evidence base through research to the support of obesity prevention interventions to standardized practice, further exploration of implementation and dissemination barriers and facilitators is warranted (Matwiejczyk, Mehta, Scott, Tonkin, & Coveney, ).…”
Section: Introductionmentioning
confidence: 99%
“…As the field is currently evolving from the gathering of an evidence base through research to the support of obesity prevention interventions to standardized practice, further exploration of implementation and dissemination barriers and facilitators is warranted (Matwiejczyk, Mehta, Scott, Tonkin, & Coveney, 2018).…”
Section: Introductionmentioning
confidence: 99%